2006
DOI: 10.1152/ajpheart.00376.2005
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine causes cerebrovascular leakage in mice

Abstract: Elevated plasma homocysteine (Hcy) is associated with cerebrovascular disease and activates matrix metalloproteinases (MMPs), which lead to vascular remodeling that could disrupt the blood-brain barrier. To determine whether Hcy administration can increase brain microvascular leakage secondary to activation of MMPs, we examined pial venules by intravital video microscopy through a craniotomy in anesthetized mice. Bovine serum albumin labeled with fluorescein isothiocyanate (BSA-FITC) was injected into a caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 89 publications
(109 citation statements)
references
References 53 publications
7
102
0
Order By: Relevance
“…Earlier we have shown that an elevated blood level of Hcy causes cerebrovascular protein leakage in mice and an increase in the formation of filamentous actin in cultured ECs. 17 Later we demonstrated that HHcy downregulates adherence junction protein, VE-cadherin and tight junction-associated protein, zonula occludin-1 (ZO-1) in cultured cells. 37 In the recent study, we found that injection of Hcy decreased messenger RNA of tight junction protein, occludin, and ZO-1 in mouse brain samples.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Earlier we have shown that an elevated blood level of Hcy causes cerebrovascular protein leakage in mice and an increase in the formation of filamentous actin in cultured ECs. 17 Later we demonstrated that HHcy downregulates adherence junction protein, VE-cadherin and tight junction-associated protein, zonula occludin-1 (ZO-1) in cultured cells. 37 In the recent study, we found that injection of Hcy decreased messenger RNA of tight junction protein, occludin, and ZO-1 in mouse brain samples.…”
Section: Discussionmentioning
confidence: 97%
“…Brain pial microcirculation was prepared for observations as previously described. 17,[29][30][31] Briefly, a mouse was placed on a stereotaxic apparatus (World Precision Instruments, Sarasota, FL, USA). The scalp and connective tissues were removed over the parietal cranial bone above the left hemisphere.…”
Section: Cranial Window Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Homocysteine-induced BBB disruption model in bEnd.3 cells was confirmed by analyzing paracellular and transcellular transport systems using Lucifer yellow and BSA-647 fluorescence probes leakage at different time points (10,20,40,60, 120 minutes) in four treatment groups. In Hcy-treated cells, significant endothelial cell permeability was observed, as evident through increased leakage of the Lucifer yellow (at 40 minutes and 60 minutes; Figure 1A) and BSA-647 (at 40 minutes to 120 minutes; Figure 1B) fluorescent dyes, which suggested that both paracellular and transcellular transport systems are affected during endothelial disruption.…”
Section: Confirming Blood-brain Barrier Disruption In Bend3 Cells Anmentioning
confidence: 95%
“…It has been reported that subclinical elevation in Hcy levels (from baseline of B3 mmol/L to B12 mmol/L) results in considerable leakage of plasma proteins (albumin and endogenous immunoglobulins) in rodent brains. [9][10][11] We earlier reported that CBS þ / À mice have high levels of Hcy (21 ± 4 mmol/L) as compared with WT (5 ± 2 mmol/L). 12 Homocysteine instigates BBB disruption by inducing redox stress and upregulating matrix metalloproteinases (MMPs), which are zinc-dependent endopeptidases that have a critical role in matrix remodeling and lead to blood-endothelial barrier leakage.…”
Section: Introductionmentioning
confidence: 97%